Day 2 Mon, October 14, 2019 2019
DOI: 10.2118/198174-ms
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-Surfactant Adsorption and Polymer Injectivity Measurements Using Reservoir Core from a Giant High Temperature and High Salinity Clastic Reservoir to Design an ASP Pilot

Abstract: This paper discusses static and dynamic adsorption experiments to evaluate surfactant and alkali consumption as well as polymer injectivity to guide well perforation design for an Alkaline Surfactant Polymer (ASP) pilot in a giant clastic reservoir in Kuwait. Alkali and surfactant consumption in the reservoir and polymer mechanical degradation near the wellbore have a significant impact on the effectiveness of the injected ASP slug to recover additional oil from the reservoir post water flooding. Aqueous solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This indicated that, over the period of five days, there was a noticeable variation that occurred in the value of SFT for this surfactant, with a slight difference between day 2 (37 mN/m) and day 3 (42 mN/m). This led to the conclusion that this surfactant is not suitable for ASP flooding, despite the fact that it has been suggested for other EOR techniques by many researchers [22,23].…”
Section: Viscosity Stability and Surface Tension Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that, over the period of five days, there was a noticeable variation that occurred in the value of SFT for this surfactant, with a slight difference between day 2 (37 mN/m) and day 3 (42 mN/m). This led to the conclusion that this surfactant is not suitable for ASP flooding, despite the fact that it has been suggested for other EOR techniques by many researchers [22,23].…”
Section: Viscosity Stability and Surface Tension Measurementsmentioning
confidence: 99%
“…The results of the adsorption and injectivity tests for the surfactants and nano-polymers are shown in Table 3. The criteria for successful application were an RF and RFF less than 1.2 and an adsorption value for every tested solution of less than 0.4 mg/1g of the core weight [23]. The RF and RFF were calculated using Equations ( 1) and ( 2), respectively.…”
Section: Adsorption and Injectivity Evaluationmentioning
confidence: 99%
“…Similarly, field applications of using an alkali alone as an EOR agent resulted in a lower oil recovery of 1-6% [5]. Although a chemical reaction between an alkali and crude oil generates in situ saponification, alkali consumption and plugging remain significant challenges [6][7][8]. The synergy of alkali and polymer injection can surpass the reported limitations of injecting them separately.…”
Section: Introductionmentioning
confidence: 99%